Protection Schemes for Fiber to the Home Access Networks with Intra Network Switch - P'ng, Won Tiang (2008)
Today, data traffic is increasing at an unprecedented rate and has pushed the existing network infrastructure to the limit particularly in the access layer. There has been many development of high speed protocols to meet the demands but the existing physical medium, which consists of copper-based network, do not have the capabilities to support these protocols. This is the reason why the problem of access network bottleneck still exists and has severely hinders the ability of service providers to offer new high-speed data services to their customer. Telephone companies are now working enthusiastically to switch from copper to fiber based network: Fiber-To-The-Home (FTTH); one that is inexpensive, simple, scalable, and capable of delivering bundled voice, data and video services to an end-user over a single network. However, there is still one obstacle, which has been generally overlooked, which is, providing protection to the access line. The fiber optics access mainly consists of a single fiber running upstream and a single fiber running downstream. If a protection path were to be created, the network provider would have to lay another 2 fibers on the network. This would increase deployment costs and also costs for the subscribers. Thus, a new way of providing fault tolerance to the system has to be introduced, by taking costs consideration and also efficiency in deploying the solution. In this thesis, three novel cost efficient schemes for providing fault tolerance to the FTTH system are introduced and methodologies to detect failures are also suggested. In 'Asynchronous Transfer Mode Passive Optical Network (APON) FTTH access network with an intra network switch' scheme, various classes of traffic, which logically represent different applications based on their Quality of Service (QoS) requirements, are defined. Access packets are switched to available working Optical Line Terminals (OLTs) according to prioritization in time of failure. In 'Time Slots Switching (TSS)' protection scheme, a new algorithm is proposed to cut off the empty portion of a time slot and the proposed switch will arrange time slots from all Optical Network Units, ONUs, (including ONU originally served by the faulty OLT) to be sent to working OLTs in round robin fashion. In 'Time Slots Redistribution (TSR)' protection scheme, protection is provided through redistribution of time slot allocated to ONUs by OLT to accommodate the ONUs of the failed OLT. The survival of the network is studied by terminating the supporting 0 LT unit one after another in simulation and observing the packet delay, packet loss ratio, the buffer occupancy and also the throughput of the switch. Results show that for different traffic classes, the number of supportable ONUs exceeds the standard value of the Full Service Access Network (FSAN) recommendations, which are 32 units per OLT. Cost analysis also shows proposed protection schemes are more cost efficient than all existing protection schemes. These results highlight the contribution of this thesis.